Developing Halal Tourism Guidance in Indonesia Based on Maqashid al-Shari'a Approach - Haerul Akmal; Setiawan bin Lahuri; Mohammad Ghozali; Nurizal Nurizal (Justicia Islamica, 2021)
The increase in the tourism sector in the world, including Indonesia, which has various lands and cultures, will captivate tourists’ attention. On the other side, with the majority Muslim population, Indonesia should keep its culture and tradition within the Islamic framework. This paper aims to develop Halal tourism in Indonesia by employing the Maqashid al-Sharia approach in four sectors: hotel, restaurant, tour, travel, and SPA. These sectors are the point of development of Halal tourism in Indonesia based on the Ministry of Tourism and Creative Economy regulation. This study explored the theories related to the five universals of Maqashid al-Sharia, including preserving din (religion), life, intellect, descendants, and wealth. The analysis results indicate that if the four sectors are used in the five universals of Maqashid al-Sharia, implementing Shariah tourism is about the Shariah label and the substance of the objectives. This study guides the development of halal tourism in Indonesia based on Islamic teachings, that is, al-Kulliyyat al-Khams on Maqashid al-Sharia.